Giant Cell Tumor of Tendon Sheath of Great Toe - Thapa, Surya Bahadur; Banskota, Bibek; Banskota, Ashok Kumar (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Giant cell tumor of the tendon sheath is an uncommon benign soft tissue tumor of the tendon sheath and synovium usually affecting the middle aged population. Only 3-10 % of Giant cell tumor of the tendon sheath occur on foot. Of them 5 - 10 % present with erosion of bone. We present a case of 30 years old male who had Giant cell tumor of the tendon sheath on the foot involving the Flexor Hallucis Longs and Extensor Hallucis Longus and eroding both the phalanges of the right great toe.